2012
DOI: 10.1167/iovs.11-7847
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Cultivated Oral Mucosal Epithelium Prepared in Fibrin-Coated Culture Dishes

Abstract: A better midterm clinical outcome was achieved with COMET of a substrate-free cell sheet than with COMET of AM as a substrate for treating severe stem cell deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 29 publications
1
73
0
2
Order By: Relevance
“…The usefulness of a serumderived fibrin substrate for cultured corneal epithelial cells has previously been reported (Hirayama et al, 2012;Rama et al, 2001Rama et al, , 2010. As fibrin substrate is absorbed after CLET and COMET, this method has some clinical benefits, in that the cultivated epithelial sheet can be transplanted directly onto the corneal surface.…”
Section: Fibrin and The Temperature-sensitive Dishmentioning
confidence: 99%
“…The usefulness of a serumderived fibrin substrate for cultured corneal epithelial cells has previously been reported (Hirayama et al, 2012;Rama et al, 2001Rama et al, , 2010. As fibrin substrate is absorbed after CLET and COMET, this method has some clinical benefits, in that the cultivated epithelial sheet can be transplanted directly onto the corneal surface.…”
Section: Fibrin and The Temperature-sensitive Dishmentioning
confidence: 99%
“…For example, in a study using rabbit models, transplanted cell sheets enhanced epithelialization of laser-ablated tissues within 5 minutes, leading to complete re-epithelization in 3 to 5 days, while in therapeutic ophthalmology, this technology enabled reduction in corneal haze after excimer laser keratectomy 5 . In addition, a cell sheet derived from a patient s oral mucosal epithelium was transplanted onto their eyes with improved clinical outcomes 6 . In adult dogs with experimentally induced dilated cardiomyopathy DCM , transplanting of a myoblastic sheet onto the left ventricle attenuated myocardial remodeling in 4 weeks with resultant improvement in cardiac function 7 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Hirayama et al [10] compared the clinical results of COMET of substrate-free sheets with those of COMET of amniotic membrane-based sheet on the corneal surface of patients with chemical injury and pseudo-ocular cicatricial pemphigoid. The authors found a better midterm clinical outcome after COMET with a substrate-free cell sheet and concluded that results with amniotic membrane grafts in the presence of chronic inflammatory ocular surface disease are less satisfactory.…”
Section: Choice Of Graft Materialsmentioning
confidence: 99%